Long non‐coding RNA H19 as a biomarker for hepatocellular carcinoma. (12th March 2022) - Rojas, Ángela; Gil‐Gómez, Antonio; de la Cruz‐Ojeda, Patricia; Muñoz‐Hernández, Rocío; Sánchez‐Torrijos, Yolanda; Gallego‐Durán, Rocío; Millán, Raquel; Rico, María Carmen; Montero‐Vallejo, Rocío; Gato‐Zambrano, Sheila; Maya‐Miles, Douglas; Ferrer, M. Teresa; et al.
Abstract: Background and Aims: Liver cancer stem cells (CSCs) could be involved in the carcinogenesis, recurrence, metastasis and chemoresistance of hepatocellular carcinoma (HCC). The aim of this study was to explore the role of lncRNA‐ H19 as a biomarker for liver cancer. Methods: LncRNA‐ H19 expression levels and the functional assays were conducted in EpCAM + CD133 + CSCs and C57BL/6J mice fed with a high‐fat high‐cholesterol carbohydrate (HFHCC) or standard diet for 52 weeks. Liver tissue and plasma samples from patients with cirrhosis, with or without HCC, were used for the analyses of gene expression and circulating lncRNA‐ H19 levels in an estimation and validation cohort. Results: EpCAM + CD133 + cells showed a stem cell‐like phenotype, self‐renewal capacity, upregulation of pluripotent gene expression and overexpressed lncRNA‐ H19 ( p  < .001). Suppression of lncRNA‐ H19 by antisense oligonucleotide treatment significantly reduced the self‐renewal capacity ( p  < .001). EpCAM, CD133 and lncRNA‐ h19 expression increased accordingly with disease progression in HFHCC‐fed mice ( p  < .05) and also in liver tissue from HCC patients ( p  = .0082). Circulating lncRNA‐ H19 levels were significantly increased in HCC patients in both cohorts ( p  = .013; p  < .0001). In addition, lncRNA‐ H19 levels increased accordingly with BCLC staging ( p  < .0001) and decreased after a partial and complete therapeutic response ( p  < .05). In addition, patients with cirrhosis who developed HCC during follow‐up showed higher lncRNA‐ H19 levels ( p  = .0025). Conclusion: LncRNA‐ H19 expression was increased in CSCs, in liver tissue and plasma of patients with HCC and decreased after partial/complete therapeutic response. Those patients who developed HCC during the follow‐up showed higher levels of lncRNA‐ H19 . LncRNA‐ H19 could constitute a new biomarker of HCC.